2018
DOI: 10.1124/jpet.117.245993
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Pharmacokinetic Drug-Drug Interactions of Direct Oral Anticoagulants: Type 5-Phosphodiesterase Inhibitors Are Inhibitors of Rivaroxaban and Apixaban Efflux by P-Glycoprotein

Abstract: Because of their lower bleeding risk and simplicity of use, direct oral anticoagulants (DOACs) could represent an interesting alternative to conventional anticoagulant treatment with vitamin K antagonists for patients with pulmonary arterial hypertension (PAH). P-glycoprotein (P-gp) plays a key role in DOAC pharmacokinetics. Type 5-phosphodiesterase inhibitors (PDE5is), a drug class commonly used in the treatment of PAH, have been shown to strongly inhibit P-gp. This work aimed to assess potential P-gp-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In another in vitro study performed by Margelidon‐Cozzolino et al, three PDE5 inhibitors (sildenafil, tadalafil, and vardenafil) strongly inhibited apixaban efflux by P‐gp suggesting potential clinically relevant DDI 29 . The maximal inhibition was higher with vardenafil and sildenafil than with tadalafil 29 …”
Section: Resultsmentioning
confidence: 97%
“…In another in vitro study performed by Margelidon‐Cozzolino et al, three PDE5 inhibitors (sildenafil, tadalafil, and vardenafil) strongly inhibited apixaban efflux by P‐gp suggesting potential clinically relevant DDI 29 . The maximal inhibition was higher with vardenafil and sildenafil than with tadalafil 29 …”
Section: Resultsmentioning
confidence: 97%
“…63 This may be explained by pharmacological issues between DOACs and the targeted PAH drugs, as some of them (bosentan, phosphodiesterase-5 inhibitors, riociguat) may provide significant drug-drug interaction with DOACs. [64][65][66] Hence, a modified bioaccumulation of DOACs in patients receiving treatment for PAH or CTEPH may be part of the absence of better safety compared with VKAs. In terms of efficacy, it has been demonstrated that VTE recurrence may be an explanation of PH recurrence after surgery, 67 highlighting the need for a highly efficient therapy.…”
Section: Confirming the Safety Of Anticoagulant Therapy In Patients Wmentioning
confidence: 99%
“…5 Moreover, a significant major drug-drug interaction (DDI) has been observed between DOACs and Type 5-Phosphodiesterase inhibitors, a major drug class in pulmonary arterial hypertension treatment. 6 Even if DOACs are associated with a decreased risk of major bleeding, such DDI may counterbalance this safety benefit, via the inhibition of P-glycoprotein.…”
Section: Direct Oral Anticoagulants: Still Too Early For Prime Time Amentioning
confidence: 99%